Sucrose stearate as a biosurfactant for development of rivastigmine containing nanostructured lipid carriers and assessment of its activity against dementia in C. elegans model - Anand A.; Arya M.; Kaithwas G.; Singh G.; Saraf S.A. (My University, 2025)
Dementia defines wide-ranging symptoms related to a decline in memory or coherent thinking. The focused endeavor of the present study was to develop and assess the efficacy of rivastigmine hydrogen tartrate (RHT) loaded nanostructured lipid carrier (RHT-NLCs) for the cure of dementia. The rise of dementia cases necessitates a curative therapy which is safe as well as effective. RHT-NLCs were developed by a modified solvent emulsification-diffusion method. Box-Behnken design was used for optimization of the developed formulation. The particle size, polydispersity index, zeta potential and percent entrapment efficiency of the optimized RHT-NLCs formulation was found to be 266 ± 0.94 nm, 0.233, −16.58 mV and 61.82 ± 2.52% respectively. RHT-NLCs displayed 81.23 ± 2.14% drug diffusion in 12 h through goat nasal mucosa and aldicarb assay exhibited increased worm paralysis due to increased concentration of acetylcholine in C. elegans model. Quantitative RT-PCR of RHT-NLCs displayed acetylcholinesterase expressing enzymes (AChE 1 and AChE 2) down-regulation, responsible for the expression of acetylcholinesterase by 4.92 ± 0.06 and 5.42 ± 0.33 respectively. Significant improvement was found in escape latency and transfer latency after treatment with RHT-NLCs in a rat model. Above results point towards the treatment/cure of dementia through RHT-NLCs developed using Compritol 888 ATO, Ryoto Sugar ester and Triacetin. © 2018